ZLc002, a putative small-molecule inhibitor of nNOS interaction with NOS1AP, suppresses inflammatory nociception and chemotherapy-induced neuropathic pain and synergizes with paclitaxel to reduce tumor cell viability. Issue 1 (September 2018) - Lee, Wan-Hung; Carey, Lawrence M; Li, Li-Li; Xu, Zhili; Lai, Yvonne Y; Courtney, Michael J; Hohmann, Andrea G
Elevated N -methyl-D-aspartate receptor activity contributes to central sensitization. Our laboratories and others recently reported that disrupting protein–protein interactions downstream of N -methyl-D-aspartate receptors suppresses pain. Specifically, disrupting binding between the enzyme neuronal nitric oxide synthase and either its upstream (postsynaptic density 95 kDa, PSD95) or downstream (e.g. nitric oxide synthase 1 adaptor protein, NOS1AP) protein partners suppressed inflammatory and/or neuropathic pain. However, the lack of a small-molecule neuronal nitric oxide synthase-NOS1AP inhibitor has hindered efforts to validate the therapeutic utility of disrupting the neuronal nitric oxide synthase-NOS1AP interface as an analgesic strategy. We, therefore, evaluated the ability of a putative small-molecule neuronal nitric oxide synthase-NOS1AP inhibitor ZLc002 to disrupt binding between neuronal nitric oxide synthase and NOS1AP using ex vivo, in vitro, and purified recombinant systems and asked whether ZLc002 would suppress inflammatory and neuropathic pain in vivo. In vitro, ZLc002 reduced co-immunoprecipitation of full-length NOS1AP and neuronal nitric oxide synthase in cultured neurons and in HEK293T cells co-expressing full-length neuronal nitric oxide synthase and NOS1AP. However, using a cell-free biochemical binding assay, ZLc002 failed to disrupt the in vitro binding between His-neuronal nitric oxide synthase1-299 and glutathione S-transferase-NOS1AP400-506, protein sequences containing the required binding domains for this protein–protein interaction, suggesting an indirect mode of action in intact cells. ZLc002 (4–10 mg/kg i.p.) suppressed formalin-evoked inflammatory pain in rats and reduced Fos protein-like immunoreactivity in the lumbar spinal dorsal horn. ZLc002 also suppressed mechanical and cold allodynia in a mouse model of paclitaxel-induced neuropathic pain. Anti-allodynic efficacy was sustained for at least four days of once daily repeated dosing. ZLc002 also synergized with paclitaxel when administered in combination to reduce breast (4T1) or ovarian (HeyA8) tumor cell line viability but did not alter tumor cell viability without paclitaxel. Our results verify that ZLc002 disrupts neuronal nitric oxide synthase-NOS1AP interaction in intact cells and demonstrate, for the first time, that systemic administration of a putative small-molecule inhibitor of neuronal nitric oxide synthase-NOS1AP suppresses inflammatory and neuropathic pain.